Computational meta-analysis of ribosomal RNA fragments: potential targets and interaction mechanisms. Issue 7 (27th March 2021) - Guan, Lingyu; Grigoriev, Andrey
Abstract: The most abundant cellular RNA species, ribosomal RNA (rRNA), appears to be a source of massive amounts of non-randomly generated fragments. We found rRNA fragments (rRFs) in immunoprecipitated Argonaute (Ago-IP) complexes in human and mouse cells and in small RNA sequencing datasets. In human Ago1-IP, guanine-rich rRFs were preferentially cut in single-stranded regions of mature rRNAs between pyrimidines and adenosine, and non-randomly paired with cellular transcripts in crosslinked chimeras. Numerous identical rRFs were found in the cytoplasm and nucleus in mouse Ago2-IP. We report specific interaction motifs enriched in rRF-target pairs. Locations of such motifs on rRFs were compatible with the Ago structural features and patterns of the Ago-RNA crosslinking in both species. Strikingly, many of these motifs may bind to double-stranded regions on target RNAs, suggesting a potential pathway for regulating translation by unwinding mRNAs. Occurring on either end of rRFs and matching intronic, untranslated or coding regions in targets, such interaction sites extend the concept of microRNA seed regions. Targeting both borders of certain short introns, rRFs may be involved in their biogenesis or function, facilitated by Ago. Frequently dismissed as noise, rRFs are poised to greatly enrich the known functional spectrum of small RNA regulation.